Quantification of polycyclic aromatic hydrocarbons (PAH4) in roasted cocoa beans using QuEChERS and dispersive liquid-liquid microextraction coupled with HPLC-FLD - Agus, Baizura Aya Puteri (2019)
Polycyclic aromatic hydrocarbons (PAHs) are carcinogenic contaminants found in cocoa beans and cocoa products during primary cocoa bean processing such as drying, storage, transportation and roasting. Currently, the determination of PAHs in cocoa product is conducted using the combination of QuEChERS (Quick Easy Cheap Effective Rugged Safe) method and dispersive liquid-liquid microextraction (DLLME) method. The combination of these two methods provides advantages such as simplicity of operation, lesser amounts of organic solvents used and high recovery for PAH quantification in cocoa products as compared to other methods such as Soxhlet extraction, accelerated solvent extraction (ASE), solid phase extraction (SPE), alkaline saponification and maceration extraction with mechanical agitation. However, according to the preliminary study, PAH4 in cocoa beans was unable to be detected and quantified using QuEChERS and DLLME coupled with gas chromatography method. Therefore, the first objective of this study was to modify analytical methods using QuEChERS and DLLME coupled with high-performance liquid chromatography with fluorescence detector (HPLC-FLD) for PAH4 recovery in cocoa bean. The results showed that by using modified DLLME parameters; 8 mL acetonitrile (dispersive solvent), 2 mL chloroform (extractive solvent), 6 mL water, centrifuge at 6000 rpm for 10 min and finally quantification by HPLC-FLD provide better recovery (68.12 – 89.16%) of PAH4 in cocoa beans. The second objective of this research was to validate the modified method based on performance characteristics provided by Regulation (EU) No. 836/2011. The validation process has shown that the modified method had met the performance criteria required by Regulation (EU) No. 836/2011. Performance characteristics such as limit of detection (LOD, 0.04 - 0.14 ng/g), limit of quantification (LOQ, 0.13 - 0.48 ng/g), repeatability (HORRATr: 0.30 – 1.25), intermediate precision (HORRATR: 0.33 – 0.77), linearity (R2 > 0.997) and recovery (52.13 to 86.23%) were determined. The third objective was the application of the modified method on the quantification of PAH4 in cocoa bean roasted at different roasting conditions (whole cocoa bean and nib roasting, different temperatures varying from 110 to 190 °C and different duration ranging from 10 to 50 min). The roasted cocoa beans’ analysis showed a significant (p < 0.05) increase in B[a]A (0.19 – 1.18 ng/g), Chrys (<0.48 – 2.60 ng/g) and B[a]P (<0.13 – 4.11 ng/g) contents with increasing temperatures (110 to 190 °C) and duration (10 to 50 min), whereas B[b]F was not detected until the temperature reached 190 °C. Total PAH4 (sum of total B[a]A, Chrys, B[b]F and B[a]P) showed a significant (p < 0.05) increase (0.19 – 7.73 ng/g) with increasing temperatures and duration. This study shows that whole cocoa bean or nib roasting methods are safe to be used since the maximum B[a]P (4.11 ng/g) and PAH4 (7.73 ng/g) presence are lower than maximum limit by Regulation EU No. 835/2011. In the present study, roasting conditions (whole cocoa beans or nibs roasting at different temperatures and duration) did significantly affect the PAH4 contents in the cocoa samples. The modified and validated method (QuEChERS and DLLME coupled with HPLC-FLD) was effective in detecting and quantifying the PAH4 in cocoa beans with high accuracy, sensitivity and precision.